A Study of Anatomy of Frontal Recess in Patients Suffering from ‘Chronic Frontal Sinus Disease’ - Sagar, G. R. S. (Springer India, 2013)
A study designed to describe the anatomical features of the frontal recess area in patients suffering from chronic frontal sinusitis. A prospective study done in adult patients admitted in our hospital between July 2009 to June 2011. Tertiary level, private ENT care centre. 50 adult patients of chronic frontal sinusitis who did not have history of previous sinus surgery. The frontal recess anatomy was studied by 2 mm slice CT scans pre-operatively. CT findings were confirmed intra operatively by meticulous dissection in frontal recess area endoscopically with aid of image guided system. A chart prepared for each patient of different anatomical variations present in frontal recess on each nasal side and analyzed. Agger nasi cell was found in 94 % of cases. The superior attachment of the uncinate was to the lamina papyraceae in 82 % of cases. Type 1 frontal recess cells were found in 44 %, type 2 in 8 %, type 3 in 48 % and type 4 in 2 % of the cases. Over all 74 % of cases had frontal recess cells. The management of frontal sinusitis is a challenge to endoscopic surgeon and as more and more rhinologists got expertise in endoscopic sinus surgery skills; the next challenge is management of frontal sinus. Hence, the need arises for more precise study of frontal recess anatomy. Detailed studies of anatomic features of the frontal recess by coronal and sagittal CT scans are very important and helpful for endoscopic frontal sinus surgery. Our study suggests that there is high prevalence of frontal recess cells in Indian population suffering from frontal sinusitis.